2015
DOI: 10.1093/heapro/dav112
|View full text |Cite
|
Sign up to set email alerts
|

Electronic health literacy of older Hispanics with diabetes

Abstract: Although the internet increases the availability of diabetes-related health information, health care consumers need to have different skills in order to obtain, interpret and evaluate such information. The eHealth literacy scale (eHEALS) was originally developed to assess consumers' perceived skills at using information technology for health. The objective of this study was to explore the experiences of older Hispanics' with type 2 diabetes in using the internet for diabetes management. This study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 17 publications
4
32
0
Order By: Relevance
“…Similarly, in a sample of elderly living with chronic disease, participants reported the Internet as a useful information source on their condition. Still, they often relied on the help of relatives and friends when assessing the information [44]. A similar strategy has been observed for Hispanic breast cancer survivors in the United States; managing online health information in their case was a responsibility they consistently shared with their offline social networks [45].…”
Section: Media Health Literacy and Ehealth Literacy In Contextmentioning
confidence: 99%
“…Similarly, in a sample of elderly living with chronic disease, participants reported the Internet as a useful information source on their condition. Still, they often relied on the help of relatives and friends when assessing the information [44]. A similar strategy has been observed for Hispanic breast cancer survivors in the United States; managing online health information in their case was a responsibility they consistently shared with their offline social networks [45].…”
Section: Media Health Literacy and Ehealth Literacy In Contextmentioning
confidence: 99%
“…A third search using the keywords, electronic health literacy and Spanish , yielded 33 articles. Of those articles, only one article was on electronic health literacy among English and Spanish language speakers (Aponte & Nokes ), four were literature reviews, and the other studies were on health literacy which either were among Spanish‐speaking Hispanics or included that population. Four hundred and twenty‐seven million people from 31 different countries speak Spanish (Lewis et al .…”
Section: Introductionmentioning
confidence: 99%
“…), Dutch (van der Vaart et al . ) and Spanish (Aponte & Nokes ). The Spanish version validation work supported the use of the instrument with that population and the research reported in this article extends that work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in a sample of elderly living with chronic disease, participants reported the Internet as a useful information source about their condition. Still, they often relied on the assistance of relatives and friends when assessing the information [42]. A similar strategy has been observed for Hispanic breast cancer survivors in the United States; managing online health information in their case was a responsibility they consistently shared with their offline social networks [43].…”
Section: Social Networkmentioning
confidence: 99%